Keputusan Kepala Daerah Tentang Penetapan Kesatuan Masyarakat Hukum Adat Sebagai Desa - Nahumury, Ryan Kevin; Nendissa, Renny Heronia; Picauly, Benjamin Carel (SANISA: Jurnal Kreativitas Mahasiswa Hukum, 2025)
Introduction: The institutionalization of the Customary Law Community (MHA) unit into a Customary Village is carried out through a determination carried out by the Regional Head. Related to the determination as a unit of MHA as a Customary Village. Provisions regarding the requirements and implementation of the determination of the MHA unit to become a Customary Village are regulated in the provisions of Law No. 6 of 2014 Article 97. The implementation of the determination of the MHA unit as a Customary Village in reality, there are those that are not designated as Customary Villages, but as Villages, even though the requirements and criteria in the provisions of Law No. 6 of 2014 have been met. The determination of MHA units in West Seram Regency as a Village and not as a Customary Village raises legal problems. Juridically, normatively, the MHA units meet all the requirements and criteria of Law No. 6 of 2014 article 97, but are not designated as Customary Villages (or in SBB Regency term referred to as state) but as Villages.Purposes of the Research: The aim of this research is Validity of the Decision of the Regional Head Regarding the Determination of the Unity of the Customary Law Community as a Village Based on Law Number 6 of 2014Methods of the Research: The research used by the author is an empirical juridical research type. The procedure for collecting legal materials by conducting research in the form of interviews and observations as well as literature studies on legal materials, namely primary legal materials and secondary legal materials. Then the legal materials that have been obtained are analyzed descriptively-qualitatively.Results / Findings / Novelty of the Research: The results obtained are the importance of determining the unity of the customary law community into a village must pay attention to various things in order to realize the welfare of the people which does not contradict the correct legal mechanism so that it does not have fatal legal consequences and is detrimental to the community.